2018 Solid-State, Actuators, and Microsystems Workshop Technical Digest 2018
DOI: 10.31438/trf.hh2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Q Monocrystalline Silicon Carbidedisk Resonators Anchored Upon a Phononic Crystal

Abstract: This work introduces a 3D design incorporating a phononic crystal to decouple a centrally-supported silicon carbide bulk acoustic wave disk resonator from its Si handle layer. By overcoming thermoelastic and anchor losses in bulk acoustic wave resonators, this scheme allows for probing the phonon-phonon dissipation limits i.e. Akhiezer loss. Using a custom silicon carbide on insulator platform, SiC disk resonators anchored upon phononic crystal were fabricated and optically measured. SiC disk resonators exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The recent development of bond and etch-back thick monocrystalline 4H silicon carbide-on-insulator (4H-SiCOI) substrates [17] and their deep reactive ion etching with high aspect ratio [18], [19] facilitate wafer-level fabrication of capacitive in-plane resonators with ultra-high mechanical Q-factors. Their frequency spectrum measurements have revealed that the elasticity of hexagonal 4H-SiC is not well-understood, evidenced by consistent discrepancy with numerical simulations from wafer to wafer [20]. Approaches to probing hexagonal SiC's mechanical anisotropy have been limited: Brillouin scattering spectroscopy in 1997 when warped SiC wafers were plagued with high-density micropipes and dislocations [21], bulk quantities in 2019 in pristine wafers [22]- [25] and-predominantly-ab initio calculations [26]- [29] with varying results.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The recent development of bond and etch-back thick monocrystalline 4H silicon carbide-on-insulator (4H-SiCOI) substrates [17] and their deep reactive ion etching with high aspect ratio [18], [19] facilitate wafer-level fabrication of capacitive in-plane resonators with ultra-high mechanical Q-factors. Their frequency spectrum measurements have revealed that the elasticity of hexagonal 4H-SiC is not well-understood, evidenced by consistent discrepancy with numerical simulations from wafer to wafer [20]. Approaches to probing hexagonal SiC's mechanical anisotropy have been limited: Brillouin scattering spectroscopy in 1997 when warped SiC wafers were plagued with high-density micropipes and dislocations [21], bulk quantities in 2019 in pristine wafers [22]- [25] and-predominantly-ab initio calculations [26]- [29] with varying results.…”
Section: Introductionmentioning
confidence: 93%
“…However, there was a consistent discrepancy between our measurement and theoryparticularly in elliptical wineglass modes; this motivated investigation into a new set of elastic constants that better reflect the mechanical properties of 4H-SiC within the framework of the SiCOI platform. As described earlier, achieving high Q is non-trivial often due to anchor losses which rely on a thorough understanding of 4H-SiC's stiffness to conform to various decoupling schemes' stringent frequency requirements [18], [20].…”
Section: B Elastic Anisotropy Refinementmentioning
confidence: 99%
“…Figure 7 outlines the 4H-SiCOI substrate's low-temperature wafer-level fabrication process. This method has garnered widespread validation across an extensive spectrum of monocrystalline 4H-SiC resonators [29,[39][40][41]. Initially, a 4H-SiC wafer was wet oxidized and bonded onto a silicon substrate with the aid of TEOS SiO2 as an intermediate bonding agent at 700°C, followed by subsequent wafer grinding and polishing, which generated the 100mm 4H-SiCOI wafer.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon Carbide mesas [11], beams [7], disks [8] and high-aspect ratio gaps [12] have been demonstrated in 4H-SiC on Insulator (SiCOI) using oxide-oxide wafer bonding and DRIE etching using SF6/O2 and SF6/Ar chemistries. Doped SiCOI technology is ideal for defining and isolating resonators and electrostatic actuators.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Recently membranes [6], perforated disks [7] and solid disks [8] have been demonstrated using DRIE of 4H silicon carbide. The center-anchored solid disks have outstanding Q > 10 6 , but the back-side-only etched membranes have low Q (<500).…”
Section: Introductionmentioning
confidence: 99%